The effect of a core antigen vaccine on health and performance of cattle diagnosed with bovine respiratory disease - Stokka, Gerald L.; Brandt, Robert T., Jr.; Kreikemeier, K.K.; Milton, T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
When studied in receiving trials at three locations, health or performance of calves receiving a core antigen vaccine was not improved.
Keywords: Beef; Core antigen; Vaccine; Health; Performance